2003
DOI: 10.1063/1.1555696
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and physical characterization of gate oxides on 4H-SiC grown in diluted N2O

Abstract: A systematic electrical and physical characterization of gate oxides on 4H-SiC, grown in diluted N2O at 1300 °C, has been performed. Electrical characterization by the high-frequency C-V technique, conductance technique, and slow trap profiling method reveals that the densities of interface and near-interface traps, and the effective oxide charge for gate oxides grown in 10% N2O are the lowest, compared to gate oxides grown in 100% and 0.5% N2O. These results are supported by physical characterizations using x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 24 publications
3
54
1
Order By: Relevance
“…2e). It has been reported that the decomposition of SiC happened during thermal nitridation and oxidation in SiO 2 /SiC system [10,19]. The decomposition of SiC was enhanced when the annealing temperature increased.…”
Section: Resultsmentioning
confidence: 96%
“…2e). It has been reported that the decomposition of SiC happened during thermal nitridation and oxidation in SiO 2 /SiC system [10,19]. The decomposition of SiC was enhanced when the annealing temperature increased.…”
Section: Resultsmentioning
confidence: 96%
“…Intensive studies have been carried out on SiC MOS-based devices and it is crucial to have a high quality gate oxide deposited or grown between a metal electrode and a SiC substrate. NitridedSiO 2 has been widely employed as gate oxide in SiC MOS-based high power devices, owing to its low interface and slow trap densities, high reliability, and low leakage current [7][8][9][10][11][12][13][14][15][16][17][18][19]. Nevertheless, the maximum permissible electric field in SiC-based devices is restricted by the nitrided-SiO 2 due to its low dielectric constant (k = 3.9) compared to SiC (k = 9.7), as scaled by the Gauss's law at the interface [20].…”
Section: Introductionmentioning
confidence: 99%
“…Because the 397.8 eV spectrum indicates that N forms three chemical bonds with Si, it is assumed that most of the N at the SiO 2 /SiC interface replaced C. Furthermore, since all the N 1s HAXPES spectra sweep toward the higher energy side, the N 1s spectra were fitted using a set of three Gaussian representations [19]. Samples at all the NO annealing temperature showed a Si 2 -N-O bonding signal strength of around 10% to 20% of the main Si-N signal value, and the existence of Si 2 -N-O bonding with a similar ratio may be assumed on the interface.…”
Section: B Haxpes and Xps Measurementsmentioning
confidence: 99%